PERANCANGAN LAPORAN KEUANGAN BERBASIS ONLINE DALAM RANGKA PENINGKATAN USAHA TAHU GORENG DI WILAYAH SUMEDANG JAWA BARAT - Arifin, Agus; Tusholihah, Mardiyah; Sanubari, Sari; Mardi, Rizqo (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
Technology is growing very rapidly which affects various fields of profession, especially in the field of Micro, Small and Medium Enterprises. Micro, Small and Medium Enterprises are one of the drivers of the nation's economy that are proven to be resistant to various economic crisis shocks. The basic problem of SMEs managers is the lack of knowledge about accounting and the making of accountable financial report formats. The purpose of this study is to design an Android-based Micro, Small and Medium Enterprises accounting application system that supports MSMEs to increase business and produce financial reports that meet accounting standards in accordance with SAK EMKM (Micro Small and Medium Entity Financial Accounting Standards). The Accounting Application System contains accounting applications for MSMEs that can compile accountable financial reports that can be learned based on android so that they can be accessed anytime and anywhere in order to increase the business of the people in the Sumedang area of ​​West Java.